High-SUVmax on FDG-PET indicates pleomorphic subtype in epithelioid malignant pleural mesothelioma: Supportive evidence to reclassify pleomorphic as non-epithelioid histology - Kadota, Kyuichi (2012)
BACKGROUND: We have recently proposed to reclassify the pleomorphic subtype of epithelioid malignant pleural mesothelioma (MPM) as non-epithelioid (biphasic/sarcomatoid) histology due to its similarly poor prognosis. We sought to investigate whether preoperative maximum standardized uptake value (SUVmax) on (18)F-fluorodeoxyglucose (FDG) positron emission tomography (PET) correlates with histologic subtype in MPM. METHODS: Clinical data was collected for 78 patients with MPM who underwent preoperative FDG-PET. We retrospectively classified the epithelioid tumors into five subtypes: trabecular, tubulopapillary, micropapillary, solid and pleomorphic. Tumors were categorized by SUVmax into two groups: low (<10.0) and high (≥10.0). RESULTS: The median overall survival of epithelioid tumors with high-SUVmax (n=12) was significantly shorter (7.1 months) than that of epithelioid tumors with low-SUVmax (n=54, 18.9 months, p<0.001) and comparable to non-epithelioid tumors (n=12, 7.2 months). Epithelioid tumors with pleomorphic subtype (n=9) had marginally higher SUVmax (mean±SD: 10.6±5.9) than epithelioid non-pleomorphic subtype (n=57, 6.5±3.2, p=0.050), and were comparable to that of non-epithelioid tumors (n=12, 9.1±4.8). Among the epithelioid tumors with high-SUVmax (n=12), 50% (n=6) showed pleomorphic subtype. In contrast, among epithelioid tumors with low-SUVmax (n=54), 6% (n=3) showed epithelioid pleomorphic subtypes (p=0.001). A positive correlation between mitotic count and SUVmax was observed (r=0.30, p=0.010). CONCLUSIONS: Pleomorphic subtype of epithelioid MPM showed higher SUVmax than epithelioid non-pleomorphic subtype and was similar to non-epithelioid histology. Preoperative SUVmax on FDG-PET in epithelioid MPM can indicate patients with pleomorphic subtype with poor prognosis, supporting their reclassification as non-epithelioid.